Unusual capillary lobular hemangioma in a pediatric patient. Case report and literature review - Navas-Aparicio, Maria del Carmen (2023)
Lobular capillary hemangioma or pyogenic granuloma is a benign non-neoplastic lesion that is mainly presented as a tissue growth in response to irritation or trauma. It is located on the skin or on the mucous membrane, with the oral mucosa being the most frequent, with the gingiva standing out, but also appearing in other places such as the lips, buccal mucosa, palate and tongue, the latter being a very unusual location. This is a report of the case of a pediatric patient who underwent a surgical procedure of frenotomy, and who subsequently presented a lesion due to trauma possibly as a consequence of local anesthesia, which forced an excisional biopsy, the histopathological diagnosis being capillary lobular hemangioma or pyogenic granuloma. Likewise, a literature review of this type of pathology is presented, with emphasis on its location in the tongue.